Dynamic vulcanisation of EPDM/PE-based thermoplastic vulcanisates studied along the extruder - Machado, A. V. (2005)
Simple blending and dynamic vulcanisation of EPDM/PE blends using the resol/SnCl2 system was studied in an extruder using a series of sampling devices. The melting of the PE pellets occurs just in front of and in the first kneading zone. Upon complete melting of the PE phase, the EPDM/PE blends reach very quickly their final morphology. Crosslinking of the EPDM phase to high levels occurs already when the PE phase is not yet fully molten. The higher the EPDM content, the higher the viscous dissipation, the higher the melt temperature and, consequently, the higher the crosslinking rate. For the EPDM/PE (50/50; w/w) TPV a transition from continuous via co-continuous to fully dispersed EPDMis observed, which is driven by crosslinking. Although the degree of crosslinking of the EPDMrubber is very high, this does not prevent phase inversion of the blend. The EPDM/PE interface is rather blurred, because PE crystalline lamellae are growing into the EPDM domains, probably because of the high compatibility between PE and EPDM (60 wt% of ethene). This study shows that dynamic vulcanisation in extruders proceeds quite differently from that in batch kneaders, where melting, mixing and crosslinking are separated in time. In extruders mass and heat transport, melting of the thermoplastic, morphology development (including dispersion and phase inversion), distribution and dissolution of (crosslinking) chemicals and crosslinking of the rubber do not occur as independent phenomena, but mutually and/or continuously interact.